SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF FRIEDELIN [2, 3-d] SELENADIAZOLE - Mehtab Parveen; Sayed Hasan Mehdi; Raza Murad Ghalib; Mahboob Alam; Rokiah Hashim; Othman Sulaiman (Universitas Gadjah Mada, 2009)
The new 1, 2, 3, selenadiazole derivative (3) was prepared from friedelin (1) via the corresponding semicarbazone (2) using Lalezari cyclization. The compounds were prepared, separated and characterized on the basis of microanalysis and spectral studies. The isolated friedelin and its selenadiazole were screened in vitro for their antimicrobial activities against various pathogenic bacterial were found to be highly active against all the selected pathogens. Compound 3 showed an inhibition zone of 14 mm and 12 mm respectively against highly resistant S. albus and C. albicans. A general mechanistic scheme for these reactions is also suggested based on current and previous results.